Tilapia genetics and culture Proceedings of the seminar-workshop on tilapia genetics and culture Held at the Freshwater Aquaculture Center, Central Luzon State Univ.on 20-22 June 1985. (Metro Manila, Philippines PCAMRD/ICLARM, 1989)
Book Series No.01; 1989
Keywords: Fish culture; Tilapia culture; Tilapia genetics